PRINCIPLES OF INTENSIVE LANGUAGE LEARNING (Лучшие интеллектуальные исследования, 2025)
Abstract: This article provides a qualitative analysis of the theoretical foundations, practical applications and effects of intensive language learning methods on learning, the methods of achieving effective support in a short time using the intensive process, organizational methods of the lesson and ways to develop the motivation of language learners are considered. The article emphasizes the role of modern technologies, interactive methods and individual enterprises.